2013
DOI: 10.1186/1757-4749-5-26
|View full text |Cite
|
Sign up to set email alerts
|

Persistent gut barrier damage and commensal bacterial influx following eradication of Giardia infection in mice

Abstract: BackgroundRecent studies of Giardia lamblia outbreaks have indicated that 40–80% of infected patients experience long-lasting functional gastrointestinal disorders after parasitic clearance. Our aim was to assess changes in the intestinal barrier and spatial distribution of commensal bacteria in the post-clearance phase of Giardia infection.MethodsMice were orogastrically inoculated with G. lamblia trophozoites (strain GS/M) or pair-fed with saline and were sacrificed on post-infective (PI) days 7 (colonizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
76
1
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(88 citation statements)
references
References 53 publications
6
76
1
5
Order By: Relevance
“…Additionally, Giardia exposure may lead to increased prevalence of perceived food intolerance in humans [10], although the cause for this reaction was not identified. The concept of food antigen translocation is supported by various reports of increased intestinal epithelial barrier permeability during infection [5, 1114]. The Global Enteric Multicenter Study (GEMS) reported that Giardia infections appear to reduce the incidence of severe diarrheal disease in children in the developing world [15].…”
Section: The Impact Of Giardiasismentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Giardia exposure may lead to increased prevalence of perceived food intolerance in humans [10], although the cause for this reaction was not identified. The concept of food antigen translocation is supported by various reports of increased intestinal epithelial barrier permeability during infection [5, 1114]. The Global Enteric Multicenter Study (GEMS) reported that Giardia infections appear to reduce the incidence of severe diarrheal disease in children in the developing world [15].…”
Section: The Impact Of Giardiasismentioning
confidence: 99%
“…In contrast, a cathepsin B-like cysteine protease secreted by Giardia can modulate immune responses by degrading CXCL8, a neutrophil attractant [48]. In addition to reducing NO production, consumption of arginine by Giardia was shown to reduce IEC proliferation [44], and infection reduced intestinal epithelial barrier function [11, 12, 14, 49]. It is reasonable to assume that this disruption is partly mediated by Giardia proteins and enzymes through excretory/secretory pathways [50].…”
Section: Protective Immunity Towards Giardiamentioning
confidence: 99%
“…It is now well known that these protozoa are constantly interacting with the intestinal microbiota, but their possible relation to imbalances in microbiota composition, termed dysbiosis, is still unclear. Giardia infection may trigger long-lasting changes in the spatial distribution of commensal microorganisms, enhancing bacterial invasiveness and inflammatory responses in the gut mucosa during the post-clearance phase [9]. Regarding E. histolytica, significant alterations of predominant gut bacteria and a depletion of some predominant genera (e.g., Bacteroides, Eubacterium, Lactobacillus) in the gut of infected patients has been described [10].…”
Section: Introductionmentioning
confidence: 99%
“…Cultures of jejunal juice from patients with active giardiasis revealed increased total bacterial load, increased abundance of Enterobacteriacae, and perturbed bile acid homeostasis (27,28). Giardia infection also causes increased bacterial loads midinfection and increased bacterial invasiveness postclearance as a sequela to intestinal barrier disruption (29).…”
mentioning
confidence: 99%